2017
DOI: 10.1093/geront/gnw197
|View full text |Cite
|
Sign up to set email alerts
|

State Regulatory Approaches for Dementia Care in Residential Care and Assisted Living

Abstract: This policy study provides a resource for researchers who do cross-state studies of dementia care in RC/AL settings and state policymakers who are updating RC/AL regulations, including those responding to a 2014 Centers for Medicare and Medicaid Services rule change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 33 publications
1
88
0
Order By: Relevance
“…The variation in states' regulations pertaining to dementia care may also be associated with variation in the prevalence of ADRD in AL across states. For example, some states require dementia-specific preadmission screening (14 states), consumer disclosure (33 states), and building design to accommodate the needs of residents with ADRD (29 states), 11 and these differences likely impact AL providers' willingness to accept residents with an ADRD diagnosis. Future research is needed to better understand the market and regulatory factors that may contribute to the state variability in the prevalence of ADRD among AL residents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variation in states' regulations pertaining to dementia care may also be associated with variation in the prevalence of ADRD in AL across states. For example, some states require dementia-specific preadmission screening (14 states), consumer disclosure (33 states), and building design to accommodate the needs of residents with ADRD (29 states), 11 and these differences likely impact AL providers' willingness to accept residents with an ADRD diagnosis. Future research is needed to better understand the market and regulatory factors that may contribute to the state variability in the prevalence of ADRD among AL residents.…”
Section: Discussionmentioning
confidence: 99%
“…However, of the seven states with lower rates of hospitalization in AL, only Connecticut requires dementia care units to be licensed. 11 It is possible that states with more stringent rules for dementia care settings have provisions that result in differential rates of hospitalization or that they admit residents with differing levels of need. However, documentation of state variation in dementia care requirements for AL is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are more than 30,000 assisted‐living facilities (ALFs) in the United States serving more than 1 million residents . Older adults who reside in ALFs typically do not require the skilled nursing care provided in nursing homes (NHs), but the prevalence of dementia and physical impairments in ALF residents suggests that ALFs and NHs may face similar challenges in ensuring quality of care . Studies have demonstrated that ALF and NH residents have comparable rates of falls and hospitalizations, which suggests that they share many of the same risk factors for these undesirable clinical outcomes …”
Section: Developing a Database Of Accurate Information: The Need For mentioning
confidence: 99%
“…The primary data source for this study is the Compendium of Residential Care and Assisted Living Regulations and Policy, 2015 Edition, developed by Paula Carder, Janet O'Keeffe, and Christine O'Keeffe (Carder et al, 2015). Funded by the Office of the Assistant Secretary for Planning and Evaluation, the Compendium summarizes and compares the RCS regulations for each of the 50 states and the District of Columbia.…”
Section: Data Sourcesmentioning
confidence: 99%